Low cycle fatigue performance of DP900 steel under cyclic shear paths. Issue 1 (27th October 2021) - Zhang, Zhongran; Yue, Zhenming; Qi, Jiashuo; Gao, Jun; Qiu, Yuliang
Abstract: In this study, a sheet fatigue shear test device is designed and applied to the low‐cycle fatigue testing of DP900 with varying strain amplitudes within the range of 0.5%–6.0%. The microstructure is analyzed by using electron backscatter diffraction, and fracture surfaces are examined via scanning electron microscopy. Results indicate that the material exhibits cyclic softening behavior after the first two cycles of hardening, with a stable softening rate and a high damage evolution rate related to loading amplitude. The variation of the hysteresis curve in the cyclic process is shown. Total plastic strain energy absorbed increases as loading amplitude decreases and it reaches the peak at approximately 1%. The life prediction model based on plastic strain energy density and strain amplitude is verified to be suitable for the cyclic shear path. The influence of microinhomogeneity on the distribution of stress and strain, especially the deformation of martensite, is closely related to the bi‐linear region of fatigue life curve.